A critical evaluation of the public sector improvement framework. Issue 2 (28th August 2019) - Rodgers, Bryan; Antony, Jiju; Penman, Derek
Abstract : Purpose: The purpose of this paper is to critically evaluate the use of the public sector improvement framework (PSIF) across public sector agencies in Scotland and explore the research gaps and consequent questions which arise. It is considered that the national promotion of a methodology for public sector improvement, while entirely legitimate, deserves independent scrutiny. Design/methodology/approach: The assertions of purpose and effectiveness of PSIF made by both the Improvement Service and European Foundation for Quality Management (EFQM) have been critically examined and independent research which would support or challenge those assertions has been explored. Findings: There are significant research gaps in the published literature which raise considerations around not only the effective deployment of EFQM but also the requirement for PSIF. The question whether there is a requirement to adapt EFQM for the public sector is also raised. Research limitations/implications: This paper explores published academic research and does not reference any internal research undertaken by either the Improvement Service or EFQM. Practical implications: Practitioners who have implemented or are considering implementing PSIF should do so from an informed perspective and be aware of the apparent lack of published research and the significant gaps and questions raised through this paper. Originality/value: No published research on PSIF and its adaptation from the EFQM business model has been identified. Given the investment and impact of implementing PSIF organisation wide, it is considered extremely valuable to raise these questions for practitioners, as well as encourage the academic community in undertaking research in this area.